Mix method/ penelitian campuran KESULITAN BELAJAR PEKERJAAN DASAR TEKNIK OTOMOTIF (PDTO) SISWA KELAS X SMK PIRI I YOGYAKARTA PADA MASA PANDEMI COVID-19 TAHUN AJARAN 2020/2021: Kesulitan Belejar Pekerjaan Dasar Teknik Otomotif (PDTO) - Ahmad Suffendi; Mulfi Hardiansyah (JURNAL VOKASI DEWANTARA (JVD), 2023)
The purpose of this study was to describe learning difficulties in basic automotive engineering work during the covid-19 pandemic. This type of research is a (mixed-method) research. Data collection techniques using questionnaires and documentation. The research instrument is a questionnaire. The result of the construct validation test conducted by expert showed that the instrument was very feasible to be used for research. The result of the validation test using a used test involving as many as 19 student showed 20 valid items. The results of the reliability test obtained that the value of Alpha = 0,871 was high. The data analysis technique used descriptive statistical analysis. The result showed that learning difficulties in Automotive Engineering Basic Work during the covid-19 pandemic were low. Learning difficulties consist of internal and external factors with the following conclusions. 1) the internal factor of learning difficulties in the Basic Automotive Engineering Work during the covid-19 pandemic which consists of low attitude and motivation. 2) external factors, which consist of family factors, school factors, and community factors with learning difficulties in Automotive Engineering Basic Work during the covid-19 pandemic are relatively low.